Marcas do tempo integral nas juventudes : um estudo de caso em um Instituto Federal do Espírito Santo - Silveira, Adriana Gomes (2017)
This study deals with full-time schools for certificate programs in secondary education and young people, specifically younger adolescents, and it has as its context for analysis their experiences in a campus of the Federal Institute of Espírito Santo, Brazil. The issue of full-time education (or extended daily school routine) in government-run schools in Brazil is not a recent one. In the case of full-time schools for secondary education, new issues are introduced in the discussions derived from other levels of education, such as those related to youth culture and lifestyle. Thus, this study narrates the experiences and impressions younger adolescents had themselves as they accompanied one another in their full-time school for the certificate program in secondary education and it undertakes, for that purpose, a qualitative research with ethnographic inspiration. It employs intensive observation, a field diary, photographic records, individual and group interviews (rounds of conversation), consultation and analysis of institutional documents and relevant legislation, and, finally, letters written by these younger adolescents. From the analysis of the narratives in the letters, this study lists five axes that permeate the passing of time: (a) full-time school; (b) leisure; (c) family; (d) friendship and (e) present and future times. These axes guided the elaboration of the script for the group and individual interviews. After the first round of conversation, and in response to the request of these adolescents, the later ones took place in various open environments of the campus: in the corridors, in the grass, among others. If, on the one hand, the analyses and conclusions reached by this study indicate the association made by young people between full-time education and a greater possibility for learning, on the other hand, the potential for the extension of their daily school time is met with the physical space inadequacy of the campus vis a vis the specificities of full-time education. The narratives of these young people also indicate that their full-time school is strongly ruled by the chronological time, and it does not take into consideration young people and their lifestyles. This research concludes that extending daily school time without a project shared by the academic community can deepen and potentialize risks, such as very long enclosure time, stress, anguish, loneliness, boredom and tiredness for young people.